Sylow Structure of Idempotent $n$-Ary Groups - Galmak, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We study idempotent n-ary groups. We describe the Sylow structure of finite idempotent n-ary groups.